PEMBANGUNAN EKONOMI MELALUI AGIHAN ZAKAT: TINJAUAN EMPIRIKAL - Ibrahim, Patmawati (Jurnal Syariah, 2008)
This article attempts to explain the ability of zakat distribution in the economic development of the ummah. The article starts by explaining the position of zakat in the life of the Muslim. It further discusses Islamic theoretical views on the positive role of zakat distribution in encountering socio economic problems in Muslim society via income redistribution, which leads to income gap reduction and poverty alleviation. Results of the empirical works from previous studies have supported the theory, proving that zakat distribution successfully reduces the income gap. At the same time, it also reduces the incidence and the burden of poverty. This article then suggests the need of a comprehensive action plan to ensure the effectiveness of zakat distribution in improving the economy of the ummah. The comprehensive action plan needs the cooperation and serious commitment from three important parties, namely, the zakat agency, the zakat recipients, and the government.